Magistrates, madonnas, and miracles: the Counter Reformation in the Upper Palatinate - Johnson, Trevor (St. Andrews studies in Reformation history, 2009)
pt. 1. The Palatinate deformed -- Forges, fortresses and farms : the Obere Pfalz in the sixteenth and seventeenth centuries -- A Protestant land, 1556-1621 -- pt. 2. The Palatinate informed -- "The odious name of a reformation" : biconfessional discontents -- "Wolves among the flock" : conversion, emigration, and resistance -- "The salt of the earth" : clerical restoration and renewal -- The return of the religious -- pt. 3. The Palatinate reformed -- Shaping a Catholic society -- "Lest such devotion should fall into decline" : sacraments, sacramentals, and the sacred image -- "All things to all" : reclaiming the saints -- "Mountains of grace" : the sacred enshrined -- The devil in the Oberpfalz